Ответы и объяснения

2013-05-21T04:43:49+04:00

5x+3y=0                         1/2(x+y)=3x+2y

y=(-5x/3) --------->       1/2x+1/2y=3x+2y

                                         1/2x-3x=2y-1/2y

                                          -5/2x=3/2×(-5x/3)

                                         -5/2x=-5/2x

                                                 x=1  -----------------> 5×1+3y=0

                                                                                         5+3y=0

                                                                                         3y=-5

                                                                                            y=-5/3